2009
DOI: 10.1111/j.1467-789x.2009.00579.x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and overweight in Canada: an updated cost‐of‐illness study

Abstract: This study is to update the estimates of the economic burden of illness because of overweight and obesity in Canada by incorporating the increase in prevalence of overweight and obesity, findings of new related comorbidities and rise in the national healthcare expenditure. The burden was estimated from a societal perspective using the prevalence-based cost-of-illness methodology. Results from a literature review of the risks of 18 related comorbidities were combined with prevalence of overweight and obesity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
143
1
15

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(164 citation statements)
references
References 33 publications
(44 reference statements)
5
143
1
15
Order By: Relevance
“…For example, Colditz (1999) estimated the direct health care costs due to obesity in the United States to be 70 billion US dollar, representing 7% of the total health care costs. Studies from other countries, like Canada (Anis et al 2009), the Netherlands (van Baal et al 2006), and Switzerland (Schmid et al 2005) found somewhat lower, but still substantial proportions of the total national health care costs that are attributable to obesity, namely approximately 4%. As to the indirect costs including the value of economic output lost because of illness, injury-related work disability, or premature death, Katzmarzyk and Janssen (2004) estimated the total costs of obesity at Can$ 4.3 billion with the majority of the costs (63%, Can$ 2.7 billion) involving indirect costs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Colditz (1999) estimated the direct health care costs due to obesity in the United States to be 70 billion US dollar, representing 7% of the total health care costs. Studies from other countries, like Canada (Anis et al 2009), the Netherlands (van Baal et al 2006), and Switzerland (Schmid et al 2005) found somewhat lower, but still substantial proportions of the total national health care costs that are attributable to obesity, namely approximately 4%. As to the indirect costs including the value of economic output lost because of illness, injury-related work disability, or premature death, Katzmarzyk and Janssen (2004) estimated the total costs of obesity at Can$ 4.3 billion with the majority of the costs (63%, Can$ 2.7 billion) involving indirect costs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Canada, the Public Health Agency of Canada (PHAC) estimated that, in 2008, obesity engendered direct costs of nearly $2 billion, 2 whereas Anis et al calculated direct costs of $6 billion for 2006. 3 The difference between the findings can be explained by the fact that Anis et al included the costs of overweight in addition to the costs stemming from obesity in their calculation and covered 18 diseases associated with excess weight, while PHAC confined itself to obesity and only 8 diseases. This article presents the results of a study on the economic burden of obesity and overweight among adults in the province of Quebec, for which no estimates have previously been produced.…”
mentioning
confidence: 89%
“…According to the American Obesity Association, nealy one third of the total US population is affected by obesity with a similar situation in Canada. A report from the National Diabetes Surveillance System indicated that approximately 25% of all Canadian adults are obese as are 10% of the children (Anis et al, 2010).…”
Section: Résumémentioning
confidence: 99%